Blended Online POPBL: uma Abordagem Blended Learning para uma Aprendizagem Baseada em Problemas e Organizada em Projetos - Sousa, Sidinei de Oliveira [UNESP] (2015)
This study is linked to the research line Practice and Formative Process in Education of Program Pos-Graduate in Education, Faculty of Science and Technology, UNESP, Presidente Prudente. Thus, this research aims to plan, implement and evaluate the methodological approach of Project Organized and Problem Based Learning in a modality that combines activities distance and face to face (Blended Learning). To meet this goal, was developed a qualitative study through a intervention research that analyzed the phenomena that occurred with the implementation of the approach Blended Online POPBL (Project Organized and Problem Based Learning) as a strategy for teaching and learning in a course Introduction to Computing in the first year of a degree in Chemistry, with students and the teacher as participants of research, the teacher also served as researcher. In principle was developed a bibliographic study about the PBL/POPBL methodology, the Blended Learning modality and the Theory of Technological Pedagogical Content Knowledge (TPACK). The empirical research started with the viability of the strategy with regard to the practical aspects such as the choice of the active model methodology and problem (POPBL used at Aalborg University, Denmark) and the development of educational resources required for its implementation, including elaboration of the problems. The Blended Online POPBL approach was implemented through a constructivist theory with the intent to develop in the student knowledge related to computing, as well as skills and attitudes. The activities of Blended Online POPBL approach focused on two levels: In the first, students interacted in a Virtual Learning Environment (VLE) and other online environments...